Safety Considerations in 3D Bioprinting Using Mesenchymal Stromal Cells - Belk, Lucy; Tellisi, Nazzar; Macdonald, Hamish; Erdem, Ahmet; Ashammakhi, Nureddin; Pountos, Ippokratis (Frontiers in Bioengineering and Biotechnology, 2020)
Three-dimensional (3D) bioprinting is an emerging technology with immense potential for the fabrication of biomimetic human tissues and grafts. One of the main components of 3D bioprinting is the bioinks composed of cells, biomaterials and a variety of molecules. Regarding the ideal cell types, mesenchymal stem cells are an attractive option. Mesenchymal stem cells are readily available reparative cells, with vast proliferative capacity and have the potential to differentiate to multiple committed cell types. Despite this, a number of drawbacks to the use of mesenchymal stem cells have been suggested throughout the literature. These concerns are primarily related to the ex vivo manipulation required for 3D bioprinting. This manuscript aims to present the current knowledge and evidence surrounding the potential risk emerging from the use of mesenchymal stem cells in 3D bioprinting.